KUALITAS PELAYANAN KANTOR KECAMATAN TERHADAP KEPUASAN MASYARAKAT DOLOK BATU NANGGAR DI KABUPATEN SIMALUNGUN - Poltak Pardamean Simarmata; Hengki Mangiring Parulian Simarmata; Doris Yolanda Saragih (Jurnal Ekonomi dan Bisnis (EK&BI), 2020)
Service quality is one of the most important in government services because society will give good value from the services of their community. The purpose of this study was to determine the magnitude of the influence of the quality of public services on community satisfaction in Simalungun district, This study used a qualitative method and the data was collected by using questioner and observation method . The sample is using 100 samples with random sampling. The data collected then tested the validity and reliability and then analyzed using linear analysis using SPSS. From this study, it can be seen that there is a positive and significant influence on service satisfaction in the Dolok Batu Nanggar sub-district of 53.8% while 46.2% is influenced by other variables not examined in this study. For further research can be develoedp using relationship management or loyalty variable.